Islamic Patriotism in General Sudirman Comic Strips of Suara Muhammadijah Magazine (1966-1967) - Zara, Muhammad Yuanda (Studia Islamika, 2022)
This paper examines 29 editions of comic serials portraying the struggle of one of the most influential military commanders in modern Indonesian history, General Sudirman, published from 1966-67 by the official magazine of Muhammadiyah, Suara Muhammadijah. By using a historical and comic studies approach, this research reveals that the comic aimed to arouse a feeling of Islamic patriotism among readers of the magazine. The still-ill Sudirman was visually depicted as a devout Muslim, whose patriotism and survival ability in guerrilla operations deep in Java’s forests during the Dutch-Indonesian war were illustrated as being rooted in his Islamic faith and his experience as a young member of Hizbul Wathan, Muhammadiyah’s boy scout group. This study sheds light on comics, a neglected product of Indonesian Islamic cultural history, which sought to renegotiate the important place of Islam during the Dutch-Indonesian war (1945-1949), amid the new opportunities presented by the political turmoil that occurred during the final phase of President Sukarno’s rule, when this comic was published.